Constructing Global Presence From The Periphery: NTB’s Parallel Diplomacy For Tourism Growth - Marjan, Lulu Wal; Dermawan, Windy (Indonesian Journal of Social Science Research, 2025)
This study examines constructing global presence from the periphery within West Nusa Tenggara (NTB)’s parallel diplomacy for tourism growth. Using a qualitative research method framed by constructivism and Kuznetsov’s theory of parallel diplomacy, the study explores how NTB, as a subnational actor, actively builds its diplomatic identity while aligning with national interests. The findings reveal that NTB’s diplomacy is not merely administrative but shaped through dynamic interactions among various stakeholders, including central and local governments, private sectors, cultural communities, and international partners. This multipactor, collaborative governance has proven effective in promoting sustainable tourism, attracting domestic and international visitors, increasing investment opportunities, and enhancing NTB’s image through major international events and the development of strategic destinations like the Mandalika Special Economic Zone. The research highlights NTB’s inclusive and adaptive approach to diplomacy as a model of how subnational entities can contribute meaningfully to national and global tourism agendas